Freedom of Religion in the Workplace: The European Court of Human Rights Decisions on Applications Made by Muslim Appellants - Begović, Nedim (Journal of Muslims in Europe, 2021)
Abstract The article analyses the case law of the European Court of Human Rights on accommodation of Islamic observances in the workplace. The author argues that the Court has not hitherto provided adequate incentives to the states party to the European Convention on Human Rights to accommodate the religious needs of Muslim employees in the workplace. Given this finding, the author proposes that the accommodation of Islam in the workplace should, as a matter of priority, be provided within a national legal framework. In Bosnia and Herzegovina, this could be achieved through an instrument of contracting agreement between the state and the Islamic Community in Bosnia and Herzegovina.